CERS6 required for cell migration and metastasis in lung cancer. Issue 20 (9th September 2020) - Suzuki, Motoshi; Cao, Ke; Kato, Seiichi; Mizutani, Naoki; Tanaka, Kouji; Arima, Chinatsu; Tai, Mei Chee; Nakatani, Norie; Yanagisawa, Kiyoshi; Takeuchi, Toshiyuki; Shi, Hanxiao; Mizutani, Yasuyoshi; et al.
Abstract: Sphingolipids constitute a class of bio‐reactive molecules that transmit signals and exhibit a variety of physical properties in various cell types, though their functions in cancer pathogenesis have yet to be elucidated. Analyses of gene expression profiles of clinical specimens and a panel of cell lines revealed that the ceramide synthase gene CERS6 was overexpressed in non–small‐cell lung cancer (NSCLC) tissues, while elevated expression was shown to be associated with poor prognosis and lymph node metastasis. NSCLC profile and in vitro luciferase analysis results suggested that CERS6 overexpression is promoted, at least in part, by reduced miR‐101 expression. Under a reduced CERS6 expression condition, the ceramide profile became altered, which was determined to be associated with decreased cell migration and invasion activities in vitro . Furthermore, CERS6 knockdown suppressed RAC1‐positive lamellipodia/ruffling formation and attenuated lung metastasis efficiency in mice, while forced expression of CERS6 resulted in an opposite phenotype in examined cell lines. Based on these findings, we consider that ceramide synthesis by CERS6 has important roles in lung cancer migration and metastasis.